The Optimized Positions for Installing Wind Turbines Based on the Advanced Programming - بدور, جهاد; اسعد, ايهم (Latakia University Journal -Engineering Sciences Series, 2022)
Wind energy is one of the most important forms of renewable energies that does not cause environmental pollution. Wind energy is characterized by its high productivity of electric energy compared to other forms of renewable energies. Therefore, the adoption of wind energy in Syria will increase the efficiency of the electric energy system and reduce its great dependence on fossil fuel sources that pollute the environment. In general, wind energy systems require suitable areas for installation, so that these areas must have sufficient specifications necessary for the operation of wind farms with high efficiency. This research aims to apply the integrated geographic information system (GIS) throughout the Syrian Arab Republic, data management and integration, and geographical data sharing, as well as conducting spatial analysis and displaying the results in the form of maps, displaying, managing and documenting spatial data in order to determine the optimal positioning of wind farms on Syrian territory. Moreover, the investment of wind farms along the Syrian coast was discussed, so that the average wind speed throughout the year reaches (1-5 m/s). Furthermore, the parameters related to the theoretical kinetic energy of the wind, and various exclusion factors such as information of wind speed, altitude, slope, main roads, railways, residential areas, industrial areas, tourism and agricultural areas are discussed.